Pengaruh Profitabilitas dan Leverage Dengan Earning Per Share Sebagai Variabel Moderating Terhadap Harga Saham Syariah Pada Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia 2019-2023 - Natasya Stifani; Ria Anisatus Sholihah (Economics and Business Faculty UNUSIA, 2024)
Stock prices fluctuate frequently, so investors must really choose the stocks to buy. Before making an investment, investors should check the financial performance of the company. To select an investment, this will be used as a basis. Investors see the company's performance by analyzing profitability and leverage ratios. By analyzing these ratios, investors can see the progress and development of a company. The purpose of this research is to analyze the effect of profitability proxied by Return On Equity (ROE) and Leverage proxied by Debt to Equity Ratio (DER) on stock prices with Earning Per Share (EPS) as a moderating variable in the Islamic mining sector listed on the Indonesia Stock Exchange 2019-2023. This research is a type of quantitative research. The data collection method in this study is documentation and literature study using a sample of 15 companies. The sampling technique used purposive sampling technique. This research uses data analysis methods with panel data regression tests with the help of Eviews Version 12. The findings of this research indicate that Return On Equity (ROE) has an effect on stock prices. Meanwhile, Debt to Equity Ratio (DER) has no effect on stock prices. Earning Per Share (EPS) does not moderate the effect of ROE and DER on stock prices. Simultaneously, Return On Equity (ROE) and Debt to Equity Ratio (DER) affect the price of Islamic shares in the mining sector listed on the Indonesia Stock Exchange 2019-2023.